Research Note on "International Consumption Risk Sharing and Monetary Policy" - Sven Blank (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This model analyzes the impact of monetary policy on international consumption risk sharing. To this end, the setup by Ghironi and Stebunovs (2008) is extended in two dimensions. First, to allow for international portfolio choices, cross-border trade of home and foreign equity is brought in. Second, to assign a non-trivial role to monetary policy, nominal price rigidities are introduced as in Bilbiie, Ghironi, and Melitz (2007). The model features incomplete goods as well as incomplete asset markets. Frictions in goods markets are given by variable iceberg-type costs when shipping goods. Financial markets are incomplete as the set of available assets cannot span all the uncertainty induced by potential shock scenarios. In addition, financial markets are not fully integrated as engagement in asset markets is costly. This research note gives technical details on the solution of the model. In the following section, the basic setup of the model as well as the main variables and equilibrium conditions of the model are briefly summarized. Section 3 presents the steady state.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: 330